Perceptions of leadership, self-confidence and leadership programs among teenage girls in Israel - Shenhav Perets; Nitza Davidovich; Eyal Lewin (Cogent Education, 2023)
AbstractThis article examines the way post-primary school contributes to the extent female teenagers perceive themselves as leaders. Based on 14 in-depth interviews among teenage girls who are attending middle and high schools in the public education system in Israel, it focuses on their personal social experiences and perceptions regarding their school as a leadership development establishment. The girls describe leaders, and themselves, as people who are tolerant of other opinions. They stress that self-confidence is a key element in becoming a leader. Leadership programs conducted in schools are viewed as empowering yet not practical. They experience an absence of role modeling and mentoring at school and express an indecisive approach from their school as a leadership development establishment.